Club form of organizing classes in the development of student sport - Павленко, Олексій (Slobozhanskyi Herald of Science and Sport, 2017)
Oleksii Pavlenko Purpose: to establish the place and importance of the club form of organizing classes in the development of student sports. Material & Methods: analysis and generalization of scientific literature and the Internet using a combination of methods of historical knowledge. Result: prerequisites for the emergence and development of student sport are revealed and have a certain sequence of events: association of people, the emergence of clubs, the creation of sports clubs, the formation of student sports clubs, the competition between educational institutions of the country clubs, association clubs in the national university sports associations, holding international meetings between the teams of sports students clubs, the emergence of international sports associations of students, holding complex international competitions. Conclusion: the introduction of the club form of organization of sports activities of youth has made student sport a global social phenomenon. It becomes relevant dissemination activities of the higher educational institutions sports club outside the student sports.